Adolescência como público-alvo: o discurso da publicidade de produtos teens na categoria higiene e beleza - Freitas, Tárcia Alcântara (2012)
This research aims to contribute to the study of the relationship between adolescence and consumption through the analysis of the publicity in products in the hygiene and beauty category that have been designed for this age group. Nowadays consumption has been a type of rite of passage into adulthood and it permeates the teenage experience in its various aspects, such as in the processes of autonomy building in relation to the parents, in the insertion in the public sphere, in the definition in relation to their own bodies, etc. I will discuss topics such as the building process and value given to personal hygiene and beauty, its consolidation along the way, and the predominant appeals of these industries in relation to the feminine public – conditions that will ensure the success of teen hygiene and beauty products. The conflict between the "inevitable body" (subject to the changes due to puberty) and the mediatic body (the one prescribed by the contents exposed by the mass media) is presented to the youth, who, immersed in a mediatic culture, face the physical alteration of the end of infanthood. The advertisements that compose the corpus have been extracted from issues of Capricho magazine. They will be analyzed through the French Discourse Analysis methodology as well some semiotics tools. Based on these procedures, it will be possible to identify the persuasion strategies used in these texts to try to persuade the public audience.